Effect of vitamin E on non-alcoholic fatty liver disease (NAFLD) in reversing the biochemical and radiological hepatic pathology - an interventional study - Divakar R.; Sugirda P; Lenin R.; Henry Daniel Raj T. (Creative Pharma Assent, 2021)
We aimed to assess the effect of Vitamin E on hepatic pathology in terms of liver enzymes and ultrasonographic (USG) findings in Non-alcoholic Fatty liver disease (NAFLD) patients. Vitamin E was administered as α-tocopherol for 12 weeks for 60 patients.  Baseline and after 12 weeks of Vitamin E therapy values of anthropometric measures, fasting blood glucose, lipid profile were estimated apart from liver enzymes and USG based assessment of liver size and Hamaguchi score. NAFLD fibrosis score (NFS), a predictor of hepatic fibrosis was evaluated pre and post treatment with Vitamin E. Significant statistical difference was noted in the reduction of Triglycerides, Cholesterol, VLDL and LDL both diabetic and non-diabetic population in our study. ALT and AST normalization was observed and the mean reduction were -38.11 (p <0.001) and -22.4 (p <0.001) respectively due to Vitamin E. Mean liver size was also decreased from 16.05 (SD±1.2) to 13.36 (SD±2.0) after 12 weeks of Vitamin E therapy. However, no significant change in NFS score was noted [baseline - 0.248 (SD±0.78) and at the end of treatment - 0.535 (SD±0.87)], indicating morphological changes were not reversed with Vitamin E. No significant difference observed for mean weight, waist circumference, body mass index (BMI), serum albumin, bilirubin and HDL levels as well as platelet count from baseline to end of treatment. Hence, Vitamin E alone would be useful in the treatment of NAFLD patients even with diabetes and irrespective of biopsy status.